Proceso de atención de enfermería escolar con énfasis en el mantenimiento ineficaz de la salud del grado inicial "A" de la escuela Julio María Matovelle - Prado Cueva, Verónica. (2014)
The present investigation called PROCESS CARE NURSING SCHOOL WITH EMPHASIS ON HEALTH MAINTENANCE INEFFECTIVE INITIAL GRADE "A" SCHOOL "JULIO MARIA MATOVELLE" is a descriptive study with intervention. Aimed to apply the Nursing Care Process, based on the model of Marjory Gordon in children Initial "A". The universe was composed 498 students, which were taken as sample 22 children / as the initial 'A', for data collection was used as techniques home visits which required an observation guide the physical environment and the interview to children and parents, and the data collection instrument according to the 11 functional patterns Marjory Gordon, the same that allowed the assessment of the health status of children. Subsequently real problems were identified and potential using NANDA, NOC and NIC taxonomy, facilitating the development of nurses Diagnosis ineffective health maintenance and related factors, because the pattern 1 Dealing perception of health was the most altered well being that 50% of children / as, from families with a history of chronic diseases such degerativas Type 2 DM, hypertension, etc.., 54.55% often suffer from respiratory diseases and are currently studying for the same diseases, 72.73% live in households with overcrowding and the presence of domiciliary animals, 59.09% of parents said they go to a doctor for children / as only when sick and have never received home visits 50%. The 40.91% of parents consume alcohol. The 90.91% have a good academic performance in the regular, 40.91% no physical violence at school and at home there is the presence of family problems in 22.73%. KEYWORDS: Care Process School Nursing, NANDA, NOC, NIC, Marjory Gordon's Functional Patterns